An empirical investigation on personal finance topics and the level of knowledge among employees at Jati Beringin Sdn Bhd - Ahmad @ Mohamed, Noor Kamariah (2014)
People now days still not aware and have limited knowledge on personal finance. Therefore, it is importance to investigate on personal finance topics and the level of knowledge with the purpose of their understanding towards any area related in personal finance. Nevertheless, there is lack of research to identify personal finance topics that affecting the level of knowledge. There are four personal finance topics are identified which are follows: budgeting and saving, insurance, retirement planning, and also credit and debt. Questionnaires were distributed to the 90 respondents. The sampling procedure adopted was stratified random sampling. The data obtain were analyzed using SPSS 2.0 which involve scale reliability, frequency analysis, descriptive analysis and Pearson Correlation Coefficient. The result indicates that for budgeting and saving, insurance, retirement planning and credit and debt have moderate significant relationship that affecting the level of knowledge on personal finance among the employees in Jati Beringin Sdn Bhd. As well, retirement planning becomes the high significant relationship due to level of knowledge on personal finance topics. The finding achieved in this study will be advantage for the company in order to increase their general knowledge and also job performance.